Achieving the Sustainable Development Goals: The Role for the G20 from China's Perspective. (July 2016) - Li, Xiaoyun; Zhou, Taidong
Abstract: Development became a G20 priority under the Korean presidency in 2010 and has remained central to global summitry ever since. Although the G20 has formally involved itself in the post‐2015 process following the St. Petersburg Summit in 2013 and emphasized the Sustainable Development Goals (SDGs) as a core priority under Turkey's presidency in 2015, the UN remains the main channel for global negotiations and discussions of the post‐2015 development agenda up to its approval and adoption in September 2015 and will continue to play the leading role in the follow‐up implementation and tracking of SDGs. The present paper argues that as the SDGs come to dominate the agenda and action of donors and issues of financing take central stage, the G20 can play an important role in facilitating the implementation of the SDGs due to its various strengths, although it also faces serious challenges. The paper also points out that as the 2016 G20 chair, China can make great contributions in advancing the implementation of the SDGs both domestically and internationally.